Estudo dos efeitos antimicrobianos e antioxidantes de óleos essenciais aplicados contra patógenos alimentícios - Di Fonzo, Izabella Andrade (Universidade Federal de São Carlos, 2024)
Essential oils are natural products originated from plants that have volatile aromatic compounds and are mostly made of monoterpenes, sesquiterpenes and phenylpropanoids metabolites. They are widely used in the pharmaceutical industry due to their power to produce pleasant odors, but they can also be used in therapeutic compounds and against the oxidation and deterioration of food by microorganisms. Food products are more prone to microbiological contamination that can lead to deterioration, causing physical and sensory changes that make the product unfit for consumption. Over the years, studies on the antimicrobial activity of essential oils have been growing more and more, but in Brazil research resources are precarious, so technological advances are smaller when compared to other countries. In this way, this work aimed to analyze the antimicrobial effects of essential oils applied against various food pathogens through existing research, since its application could become an alternative in the future for the replacement of artificial chemical additives. For this, a search was carried out on academic sites like Science Direct and Capes Periodic on the subject, and the studies were ordered according to the analyzed requirements. Therefore, several antimicrobial effects were verified against food spoilage bacteria at different concentrations, in addition to different inhibitory effects based on the diameter of the halos. Finally, it was found that it is still necessary to carry out further experiments involving the ability of oils to combat microorganisms of food origin, ensuring that there will be no changes in the sensory and chemical composition of foods.
Study of the antimicrobial and antioxidant effects of essential oils applied against food pathogens
Keywords: Atividade Antimicrobiana; Antioxidante; Deterioração Alimentar; Antimicrobial Activity; Antioxidant; Food Spoilage; CIENCIAS EXATAS E DA TERRA::QUIMICA